Effect Of Life Style Risk Factors on Prevalence of Hypertension in A Defined Urban Population of Rewa - Singh, Sandeep; Dubey, Deepak Kumar; Kushwah, S S; Patel, Meena (National Journal of Community Medicine, 2012)
Introduction: Hypertension is a modern day’s epidemic and it is becoming a public health emergency worldwide, especially in the developing countries. It has been observed that cardiovascular diseases are increasing in developing countries 1, 2 and it has been estimated that CVD will be the major cause of morbidity and mortality in these countries by the year 2020.3 Materials and Methods: Cross sectional study carried out from July2010- June 2011 in general population of Rewa city. Total 300 were studied (171 males and 129 females). The study had two principal components: the administration of a questionnaire and clinical examination. Information was collected on demographic characteristics and risk factors for hypertension. Chi-square test was applied wherever necessary. Results: Overall prevalence of hypertension was found to be 21.3 %( 64/300). Among 64(21.3%) hypertensive’s, only 23(35.9%) were aware about their hypertensive status & among these known hypertensive 17(73.9%) were on regular treatment. Association between BMI and hypertension was statistically significant (p<.0001). Among 171 males 15 (8.8%) were having WHR >1 and among 129 females 42 (32.5%) were having WHR > 0.85. Prevalence of hypertension was significantly (p<.0001) higher, i.e. 40% (06), among males having WHR >1 and 21.4% (09) among females having WHR >0.85. Conclusion: Here it was observed that one fifth of general public’s are hypertensive which suggests that peoples should be screened regularly. Life style affects blood pressure which can be seen from this study that’s why healthy habits should be promoted amongst general public by different types of interventions.